Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1051/0004-6361/201936645
|View full text |Cite
|
Sign up to set email alerts
|

Hic sunt dracones: Cartography of the Milky Way spiral arms and bar resonances with Gaia Data Release 2

Abstract: In this paper we introduce a new method for analysing Milky Way phase-space which allows us to reveal the imprint left by the Milky Way bar and spiral arms in the stars with full phase-space data in Gaia Data Release 2. The unprecedented quality and extended spatial coverage of these data enable us to discover six prominent stellar density structures in the disc to a distance of 5 kpc from the Sun. Four of these structures correspond to the spiral arms detected previously in the gas and young stars (Scutum-Cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(113 citation statements)
references
References 75 publications
11
92
3
Order By: Relevance
“…Mixing these coordinate systems can confuse the interpretation. For example, it has been suggested that by moving stars to their guiding radius, the Milky Way spiral structure is visible as ridge-like overdensities in the Gaia data (Khoperskov et al 2020). However, in this work, we show that these features are in fact the known kinematic moving groups, both in the L z − φ and the v R − v φ planes.…”
contrasting
confidence: 62%
“…Mixing these coordinate systems can confuse the interpretation. For example, it has been suggested that by moving stars to their guiding radius, the Milky Way spiral structure is visible as ridge-like overdensities in the Gaia data (Khoperskov et al 2020). However, in this work, we show that these features are in fact the known kinematic moving groups, both in the L z − φ and the v R − v φ planes.…”
contrasting
confidence: 62%
“…There is more than one feature in the local kinematics that looks like the bar OLR's velocity flip. But only one can be the true OLR (if at all visible) and the others will be related to other bar resonances (e.g., Monari et al 2019a;Hunt & Bovy 2018;Asano et al 2020) and spiral arms (De Simone et al 2004;Chakrabarty 2007;Quillen et al 2018;Michtchenko et al 2018;Hunt et al 2019;Khoperskov et al 2020;Hunt et al 2020). Our angle-based method provides additional constraining evidence.…”
Section: Comparing the Action-and Angle-based Methods For The Olrmentioning
confidence: 94%
“…(B) Spiral arm models can create ridges just as strong as those observed in the Gaia data (e.g., De Simone et al 2004;Antoja et al 2009;Sellwood et al 2019;Hunt et al 2019). Work by Quillen et al (2018) and Khoperskov et al (2020) associates the main features we see in the local data not with the bar resonances, but with the MW's spiral arms as identified by Reid et al (2014) and Xu et al (2016): the 'Hat' to the Perseus arm (see also Hunt et al 2017), 'Sirius' to the Local Arm, the 'Horn' (at ( , ) ∼ (50, −20) km/s) to the Sagittarius arm, 'Hercules' to the Scutum arm. Spiral arms could even completely obscure bar resonances (e.g., Fujii et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Criteria of this kind have been tested using better N-body models and they show that the exact value of µ depends on a number of parameters of the galactic subsystems that determine the properties of the bulge, the gaseous disk, the radial profile of the dark matter, etc. [22,27,81,89,123]. Let us estimate the influence of the relative mass of the halo on the velocity dispersion of stars that are close to the boundary of stability of the system.…”
Section: Disk Kinematics In Central Regionsmentioning
confidence: 99%
“…Masers are the most important source of information for the determination of the morphology of the spiral pattern in the Milky Way galaxy [24]. Complementing the maser data, the GAIA astrometric mission [25][26][27][28][29] has recently provided positions and kinematics for more than a billion stars in the Milky Way. This will enable us to more reliably infer the morphology of the spiral pattern in our own galaxy.…”
Section: Introductionmentioning
confidence: 99%